The Poetry of Yahya Al-Ghazal: A Sociological Study - Abbas, Prof. Dr. Anahid Abdul Amir Abbas; Fayyad, Prof. Dr. Israa Khalil Fayyad (Sulaimani Journal for Humanities, 2026)
Yahya al-Ghazal (d. 250 AH) stands out among classical Arab poets for his sharp social critique. His poetry addresses widespread negative phenomena in his society, such as hypocrisy, deceit, mockery, the negative portrayal of women, and the age disparity in marriage between men and women. Through his poetic voice, al-Ghazal not only highlighted these issues but occasionally proposed solutions and moral reflections. Social criticism in poetry, therefore, emerges as a significant theme in his work. Poetry served as an effective medium for al-Ghazal to express his philosophical outlook and social concerns. His verses shed light on the social and ethical conditions of his time, engaging deeply with the realities of his community. His poetry is distinguished by its intellectual depth, sociological insight, and symbolic richness, reflecting the concerns of the human condition amid profound societal change. This study adopts a descriptive-analytical approach within the framework of the sociology of literature. It begins with an introduction to the poet's life and the historical context in which he lived. The study is divided into two main sections: 1. The first explores the concept of sociology and its relationship with literature. 2. The second examines key sociological, social, and ethical themes in al-Ghazal's poetry, offering a critical and artistic analysis of selected texts The research concludes with a summary of key findings and is supported by a comprehensive list of sources and references.
Keywords: Yahya alGhazal; sociology; literature